(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
This research consists of the results of 21 pharmaceutical OECD industries in the period between 2004 and 2009. The main objective of paper is to measure international trade and competitiveness of pharmaceutical industry within observed OECD countries. The methodology in the paper is based on the application of various indicators which include intra-industry trade, trade balance, import penetration indicator, composition of manufacturing exports and other relevant indicators The main research results include facts in the measuring international trade and competitiveness, estimation of the position of the pharmaceuticals of the observed OECD countries, especially on external market, and recommendations and proposals for reaching a higher level of international competitiveness. Keywords: international competitiveness, international trade, OECD countries, pharmaceutical industry